2016
DOI: 10.1523/jneurosci.2402-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Occipital Cortex in Resolving Perceptual Ambiguity

Abstract: Editor's Note: These short, critical reviews of recent papers in the Journal, written exclusively by graduate students or postdoctoral fellows, are intended to summarize the important findings of the paper and provide additional insight and commentary. For more information on the format and purpose of the Journal Club, please see http://www.jneurosci.org/misc/ifa_features.shtml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…As anticipated, increasing ambiguity was related to a network of brain regions typically associated with salience processing and the explicit resolution of ambiguity: bilateral anterior insula, sensory-motor/dorsal anterior cingulate cortex, and inferior frontal regions [49,50] (table 1 and figure 2). Furthermore, increasing ambiguity was associated with greater activity in the occipital cortex, a region that is also implicated in the resolution of perceptual ambiguity [51], and greater activity in the right fusiform gyrus, which is typically associated with configural face encoding [52][53][54]. No regions showed significant associations with increasing Black prototypicality at our whole-brain thresholds (see electronic supplementary material, table S1 for neural activity in response to decreasing ambiguity and increasing White prototypicality).…”
Section: (B) Conservatism Tracked Neural Sensitivity To Ambiguitymentioning
confidence: 85%
“…As anticipated, increasing ambiguity was related to a network of brain regions typically associated with salience processing and the explicit resolution of ambiguity: bilateral anterior insula, sensory-motor/dorsal anterior cingulate cortex, and inferior frontal regions [49,50] (table 1 and figure 2). Furthermore, increasing ambiguity was associated with greater activity in the occipital cortex, a region that is also implicated in the resolution of perceptual ambiguity [51], and greater activity in the right fusiform gyrus, which is typically associated with configural face encoding [52][53][54]. No regions showed significant associations with increasing Black prototypicality at our whole-brain thresholds (see electronic supplementary material, table S1 for neural activity in response to decreasing ambiguity and increasing White prototypicality).…”
Section: (B) Conservatism Tracked Neural Sensitivity To Ambiguitymentioning
confidence: 85%
“…As our results cast doubt on prior cTBS studies, also the functional fractionation between IPS and pSPL (from Kanai et al 2010 and will have to be reexamined, as it is based on relatively weak cTBS evidence from small samples. Also, a single pulse TMS-EEG study revealed no systematic difference between IPS and SPL stimulation in neither behaviour nor evoked EEG signal (Schauer et al, 2016), and our prior online 2-Hz TMS study did not reveal any effect during SPL stimulation, while revealing a lengthening of percept durations when disrupting IPS (Zaretskaya et al, 2010). As shown in Table 1, the key inconsistency among non-cTBS studies remains between the lowest-powered study that did not include a vertex control and Zaretskaya et al (2010).…”
Section: Synthesis and Conclusionmentioning
confidence: 76%
“…Electrophysiological measurements on frontal areas of macaques reveal robust responses that correlate with and precede perceptual switches, even independent of behavioural responses (Panagiotaropoulos et al, 2012;Kapoor et al, 2022;Dwarakanath et al, 2023). And, although similar transient responses exist in posterior sensory cortices (de Jong et al, 2016), new evidence suggests that these could be the results from feedback from anterior higher-level non-sensory areas (Grassi et al, 2016;de Jong et al, 2020).…”
Section: Evidence For a Causal Parietal Involvement In Multistabilitymentioning
confidence: 93%
“…And, although similar transient responses exist in posterior sensory cortices ( de Jong et al. 2016 ), new evidence suggests that these could be the results from feedback from anterior higher-level non-sensory areas ( Grassi et al. 2016a , de Jong et al.…”
Section: Discussionmentioning
confidence: 98%